Laminar Flow Through A Double Elbow Geometry With Lattice Boltzmann Numerical Method - Muhamad Zuhairi, Sulaiman (2008)
This paper presents a lattice Boltzmann method for the simulation of laminar flow through double elbow geometry. The lattice Boltzmann method was built up on the D2Q9 model and the single relaxation time called the lattice-BGK method. The dependence of reattachment length on the Reynolds number is determined. Results show that the flow was found to be strongly dependent on Reynolds number and two-dimensional behavior for Reynolds numbers below approximately 400. Comparable results were obtained between the present approach and those from a Navier-Stokes solver. Keywords: Double elbow geometry, laminar fluid flow, lattice Boltzmann method